PENGARUH PENGGUNAAN BAHAN AJAR BERBASIS MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) TERHADAP PEMAHAMAN MATEMATIS MAHASISWA - Sri Lestari Manurung; Elfitra Elfitra; Suci Frisnoiry (Universitas Negeri Medan, 2018)
Abstract: The Effect of Using Learning Materials Based on Creative Problem Solving (CPS) Learning Model on Student Mathematical Understanding. The purpose of this study was to examine the improvement of students 'mathematical understanding skills through learning by using teaching materials based on the Creative Problem Solving (CPS) model compared to the students' mathematical understanding ability through learning without using teaching materials based on CPS models. This research is experimental research. The selection of samples used as the experimental group and the control group was made randomly (random cluster sampling). The sample of this study is the 2018 DIK-C class students at Dikmat FMIPA Unimed Study Program, which amounted to 35 people as the experimental class and the DIK-E 2018 class, Dikmat FMIPA Unimed Study Program, which totaled 37 people as the control class. The data in this study were analyzed using descriptive statistical analysis and inferential analysis. The inferential analysis used is the analysis with the t-test, by analyzing the mathematical understanding ability of students in both groups. The results showed that students' mathematical understanding ability in the experimental class was better than the mathematical understanding of students in the control class, and students were more active when learning using CPS model-based teaching materials.Keywords: CPS models, mathematical understanding.Abstrak: Pengaruh Penggunaan Bahan Ajar Berbasis Model Pembelajaran Creative Problem Solving (Cps) Terhadap Pemahaman Matematis Mahasiswa. Tujuan dari penelitian ini adalah untuk menelaah peningkatan kemampuan pemahaman matematis mahasiswa melalui pembelajaran dengan menggunaan bahan ajar berbasis model Creative Problem Solving (CPS) dibandingkan dengan kemampuan pemahaman matematis mahasiswa melalui pembelajaran tanpa menggunakan bahan ajar berbasis model CPS. Penelitian ini merupakan penelitian eksperimen. Pemilihan sampel yang dijadikan kelompok eksperimen dan kelompok kontrol dilakukan secara random (random cluster sampling). Adapun sampel penelitian ini adalah mahasiswa kelas DIK-C 2018 Prodi Dikmat FMIPA Unimed yang berjumlah 35 orang sebagai kelas eksperimen dan kelas DIK-E 2018 Prodi Dikmat FMIPA Unimed yang berjumlah 37 orang sebagai kelas kontrol. Data dalam penelitian ini dianalisis dengan menggunakan analisis statistik deskriptif dan analisis inferensial. menganalisa kemampuan pemahaman matematis mahasiswa pada kedua kelompok. Hasil penelitian menunjukkan bahwa kemampuan pemahaman matematis mahasiswa pada kelas eksperimen lebih baik dibandingkan dengan pemahaman matematis mahasiswa pada kelas kontrol, serta mahasiswa lebih beraktivitas saat pembelajaran dengan menggunakan bahan ajar berbasis model CPS.Kata kunci: Model CPS, Pemahaman matematis.